Effect of tramadol on metamizol pharmacokinetics and pharmacodynamics after single and repeated administrations in arthritic rats - Luis Alfonso Moreno-Rocha; Francisco Javier López-Muñoz; José Raúl Medina-López; Adriana Miriam Domínguez-Ramírez (Elsevier, 2016)
Combined administration of certain doses of opioid compounds with a non-steroidal anti-inflammatory drug can produce additive or supra-additive effects while reducing unwanted effects. We have recently reported that co-administration of metamizol with tramadol produces antinociceptive effect potentiation, after acute treatment. However, none information about the effect produced by the combination after chronic or repeated dose administration exists. The aims of this study were to investigate whether the antinociceptive synergism produced by the combination of metamizol and tramadol (177.8 + 17.8 mg/kg, s.c. respectively) is maintained after repeated treatment and whether the effects observed are primarily due to pharmacodynamic interactions or may be related to pharmacokinetics changes. Administration of metamizol plus tramadol acute treatment significantly enhanced the antinociceptive effect of the drugs given alone (P < 0.05). Nevertheless, this effect decreased about 53% after the chronic treatment (3 doses per day, for 4 days). No pharmacokinetic interaction between metamizol and tramadol was found under acute treatment (P > 0.05). The mechanism involved in the synergism of the antinociceptive effect observed with the combination of metamizol and tramadol in single dose cannot be attributed to a pharmacokinetic interaction, and other pharmacodynamic interactions have to be considered. On the other hand, when metamizol and tramadol were co-administered under repeated administrations, a pharmacokinetic interaction and tolerance development occurred. Differences found in metamizol active metabolites' pharmacokinetics (P < 0.05) were related to the development of tolerance produced by the combination after repeated doses. This work shows an additional preclinical support for the combination therapy. The clinical utility of this combination in a suitable dose range should be evaluated in future studies.